Entrepreneurial Values and Entrepreneurial Competencies in Business Sustainability - Anam, Hoirul (Universitas Islam Tribakti Lirboyo Kediri, 2025)
ABSTRACT Purpose - Entrepreneurship has a positive impact on Indonesia's still-developing economic growth. The urgency of achieving an advanced Indonesia must also be supported by good entrepreneurial development.Design/Methods – This research is descriptive qualitative to know the role of entrepreneurial values and competencies in the business continuity process of TB. Nusantara Ilmu Kediri.Findings – This research is descriptive qualitative to know the role of entrepreneurial values and competencies in the business continuity process of TB. Nusantara Ilmu Kediri. The results of this study indicate that entrepreneurial values have a good impact on the formation of a strong and resilient entrepreneurial character and have a role in the level of business continuity. Entrepreneurial competence has a role in a business's development, performance, and success. Research Implications/Limitations – The background of the lack of certification in the entrepreneurial world is caused by a lack of knowledge, socialization, and high costs.Originality/Value – Entrepreneurial values and competencies that are well implemented by entrepreneurs will have a good impact on the management and success of their businesses.Keywords: Entrepreneurial Values, Entrepreneurial Competencies, Certification, Business Sustainability